2019
DOI: 10.3892/etm.2019.7556
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenesis and bone regeneration by mesenchymal stem cell transplantation with danshen in a rabbit model of avascular necrotic femoral head

Abstract: The present study aimed to explore the potential of combined treatment with mesenchymal stem cells (MSCs) and danshen for angiogenesis and bone regeneration in a rabbit model of avascular necrosis of femoral head (ANFH). A rabbit model of ANFH was established using the Shwartzman reaction with methylprednisolone and Escherichia coli endotoxin injection. Magnetic resonance imaging (MRI) and histopathological examination were used to evaluate the rabbit model of ANFH. The rabbits were randomly divided into the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 46 publications
(45 reference statements)
2
11
0
Order By: Relevance
“…To date, ANFH is still a great challenge to orthopedic surgeons as the exact mechanisms remain unclear. It is characterized by bone ischemia and destruction of the microstructure, resulting in increased adipose vacuoles and collapse of the femoral head ( Pierce et al, 2019 ; Wu et al, 2019 ). BMSCs are capable to differentiate into various cell types including osteoblasts, adipocytes, myoblasts and chondrocytes ( Liu R. et al, 2019 ; Zheng et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…To date, ANFH is still a great challenge to orthopedic surgeons as the exact mechanisms remain unclear. It is characterized by bone ischemia and destruction of the microstructure, resulting in increased adipose vacuoles and collapse of the femoral head ( Pierce et al, 2019 ; Wu et al, 2019 ). BMSCs are capable to differentiate into various cell types including osteoblasts, adipocytes, myoblasts and chondrocytes ( Liu R. et al, 2019 ; Zheng et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…18 A previous study conducted by Wu and team stated that post-transplantation of MSCs in a rabbit model of avascular necrosis of femoral head can enhance the BMP-2 expression level that stimulates in vivo revascularization and bone remodeling of the afflicted area. 34 Meanwhile, a study conducted by Liu and team mentions the significantly increased expression of BMP-7 in BMSCs in vitro culture indicating that the enhancement of BMP-7 expression can be used as BMSCbased cell therapy for osteoarthritis. 35 The results of those studies were in line with and support the findings of the authors that showed post-transplantation of SHED can stimulate the enhancement of BMP-2 and BMP-7 in the alveolar bone defect area.…”
Section: Discussionmentioning
confidence: 99%
“…The researchers found a high level of interleukin-6 and tumor necrosis factor-α at an advanced stage of FHN. Thus it was found that cytokine activity accelerated when used in combination with growth factor, which can be further used in future studies [70][71][72][73][74][75][76] .…”
Section: Femoral Head Osteonecrosis Treatment Through Growth Factorsmentioning
confidence: 99%